ANALISIS PERBANDINGAN LAJU INFILTRASI PADA RUANG TERBUKA HIJAU DI WILAYAH KOTA BANJARBARU - M. Arterio Widi Admaja; Eddy Nashrullah (Lambung Mangkurat University Press, 2026)
In the urban hydrological system, Green Open Spaces (GOS) function as rainwater infiltration areas. However, rapid urban development in Banjarbaru City has led to a reduction in green areas, resulting in decreased soil infiltration capacity and increased surface ponding. This study aims to evaluate the effectiveness of Green Open Spaces as groundwater recharge areas. Infiltration testing was conducted using a double-ring infiltrometer at five-minute intervals, with three repetitions at each location until steady-state conditions were achieved. The results were then analyzed using the Horton equation and the actual infiltration method. The findings indicate that Bumi Cahaya Bintang Green Open Space exhibits the highest infiltration rate, reaching 67.78 cm/hour based on the Horton method and 52.8 cm/hour based on actual measurements, while the lowest infiltration rate was observed at Taman Mawar Lansia, with values of 24.97 cm/hour (Horton) and 16 cm/hour (actual). The Horton method demonstrates a consistent trend with the actual measurements and can therefore be considered representative. Overall, Green Open Spaces in Banjarbaru City function effectively as infiltration areas, with infiltration rates classified as rapid to very rapid.